Teacher's Job Stress Associated with a Virtual Class Application and Work Duration during Covid-19 Pandemic - Kurnia Ardiansyah Akbar; Reny Indrayani; Adinda Jasmine Rohmaniah (Universitas Airlangga, 2022)
Introduction: The increasing number of Covid-19 cases in Indonesia triggers fear and anxiety in the community and causes stress. Teachers who work are at risk of experiencing job stress. The change in the learning system from face-to-face to distance learning requires teachers to adapt to the new technology applied. The purpose of this research was to analyze the relationship between the understanding of the Google Classroom application and duration of work during the Covid-19 pandemic with job stress. Methods: This research is an analytical research with a cross sectional approach. The research was conducted in 8 public high schools in Nganjuk District, and the samples were 115 teachers. Data retrieval was done by using an online questionnaire via Google Form. The variables in this research were the understanding of the Google Classroom (knowledge, perceptions of the usefulness and ease of use), work duration and job stress. Bivariate analysis used Spearmans’ Rho correlation test to determine the relationship between variables. Results: Most respondents had a moderate level of knowledge, and most of them had a fairly good perception of the usefulness and ease of use of the Google Classroom application. The duration of work that most respondents had was 2 hours, and the highest category of job stress was mild stress. Conclusion: The understanding of the Google Classroom application (knowledge of the Google Classroom application, the perception of the usefulness of the Google Classroom application and the perception of the ease of use of the Google Classroom application) and the duration of work had a significant relationship with job stress among public high school teachers in Nganjuk District during the Covid-19 pandemic.